Instrumen Keuangan Syariah Murabahah, Bai Istijrar dan Bai Ul-Wafa - Helda Rostiani; Aditya Aditya; Lince Bulutoding (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This article examines murabahah as the most dominant financing instrument in Indonesian Islamic banking. The basic concept, legal basis, and various practices of murabahah that have developed are described through library research on classical fiqh works, DSN-MUI fatwas, and Bank Indonesia regulations. The results show that murabahah requires bank ownership of goods, fixed margins, price transparency, and a prohibition on recognizing late fees as income. Three models can be applied in the field: direct purchase by the bank, bank payment by direct delivery of goods to the customer, and the most common wakalah model. However, this model is shariah risky if the contract is made before the goods are legally owned by the bank. This article highlights the need for standardization of procedures to be consistent with muamalah fiqh while meeting contemporary regulatory requirements, and recommends further research on the harmonization of murabahah accounting between AAOIFI and IFRS. The dominance of murabahah covers around 60% of the financing portfolio.